DETEKSI MOLEKULER VIRUS PENYEBAB PENYAKIT MOSAIK PADA TANAMAN TEBU - , ANGGI AMALIA, Dr. Ir. Sedyo Hartono, M. P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sugarcane is an important commodity that has strategic role in the plantation sector. Crop production is constrained by the presence of Sugarcane mosaic virus (SCMV) and/or Sugarcane streak mosaic virus (SCSMV) cause loss of sugarcane production. To improve control strategies of the disease, the detection of the causal agents are needed. This study aims to determine virus particle morphology